If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (2x + -5) + (2x + 2) = 62 Reorder the terms: x + (-5 + 2x) + (2x + 2) = 62 Remove parenthesis around (-5 + 2x) x + -5 + 2x + (2x + 2) = 62 Reorder the terms: x + -5 + 2x + (2 + 2x) = 62 Remove parenthesis around (2 + 2x) x + -5 + 2x + 2 + 2x = 62 Reorder the terms: -5 + 2 + x + 2x + 2x = 62 Combine like terms: -5 + 2 = -3 -3 + x + 2x + 2x = 62 Combine like terms: x + 2x = 3x -3 + 3x + 2x = 62 Combine like terms: 3x + 2x = 5x -3 + 5x = 62 Solving -3 + 5x = 62 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 5x = 62 + 3 Combine like terms: -3 + 3 = 0 0 + 5x = 62 + 3 5x = 62 + 3 Combine like terms: 62 + 3 = 65 5x = 65 Divide each side by '5'. x = 13 Simplifying x = 13
| r+42=8(r-10.5) | | 40*15+55-x=650 | | 50*6-x=190 | | -12=3(2x-10) | | x^6+2x^5-7x^4+4x^3= | | -5(4-3)=2(1-8)+11 | | y-x+y=-1 | | 21.42=-3x+6x+.43 | | 15+.39x=50 | | -.8a-8=.2a | | 24=6(7k-10) | | Y-87.4=0 | | 6x+20=4x-172 | | 60*x-35=325 | | 45=5(2x+7) | | 30*x+83=353 | | 24-64= | | w-13.7=22.8 | | 6+4x+6x=11.45 | | -1=2x-y | | 2+y/2=-1 | | 520/10+x=402 | | 3-7x-.25x=-4.25 | | x*9+74=146 | | 3(2y-1)+6y= | | 4y-6=8+4a | | -6x-2y=-8 | | =-5a+4 | | 64/5/3= | | -8x+2x-16=5x+7x | | (0.00015*54.6)+1.0020= | | 6.2g=-.2g |